THE CHARACTERISTIC OF ROBUSTA POWDER COFFE IN VARIOUS SIZE TYPES and COFFE WEIGHT ON SACHETS - Tri Agustina; Devi Silsia; Lukman Hidayat (AGRITROPICA : Journal of Agricultural Sciences, 2020)
This research aims to determine the performance influence of sachets on various sizes of bags and the weight of coffee to the characteristics of the brew of coffee bags. The study uses a completely random design with 2 treatment factors, the first factor of the volume of contents in the bag and the second factor of the packaging bag size. Analyzed With ANOVA dan when the effect is noticeable. It will be followed by using a DMRT at  5%. significant levels. The research at moisture and ash content is suitable for the raw material of coffee bags. Coffee Sari qualified SNI is on the treatment of the volume of 1/4 content and small bag size with a yield of 22.02% coffee juice. The results of the analysis on the missing coffee weight test were obtained the highest value found in the volume of the 1/3 content with a large bag size resulted in 2.73 grams of lost coffee weight. The lowest value is on the 1/2 content volume and the medium size is 0.17 grams. The sensory test was derived that the panelists preferred it to the size of a large bag and the appropriate volume of contents to fill the bag with a volume of 1/3.Keywords: Bag size and coffee weight, Coffee characteristics.